Comprehensiveness of online sources for patient education on otosclerosis - Cırık, Ahmet Adnan; Yiğit, Yeşim Esen; Tekin, Ahmet Mahmut; Duymaz, Yaşar Kemal; Şahin, Şamil; Erkmen, Burak; Topsakal, Vedat (Frontiers in Surgery, 2024)
Purpose: To assess readability indices of websites including education materials on otosclerosis. Methods: We performed a Google search on 19th April 2023, on the term: “otosclerosis”. First 50 hits were collected and analyzed. The websites were categorized into two groups: websites for health professionals and general websites for patients. Readability indices were calculated using the website https://www.webfx.com/tools/read-able/. Results: In total, 33 websites were eligible and analyzed (20 health professional oriented and 13 patient-oriented websites). When patient-oriented websites and health professional oriented websites were individually analyzed, mean Flesch reading ease (FRE) scores were found to be 52.16 +- 14.34 and 46.62 +-10.07 respectively. There was not a significant difference between the two groups when statistical analysis was carried out. Conclusion: Current patient education material available online related to otosclerosis is written beyond the recommended sixth grade reading level. The quality of good websites is worthless to the patients if they cannot comprehend the text. Keywords: Otosclerosis, readability, comprehensiveness, online sources